ENHANCING SPEAKING PROFICIENCY THROUGH FLIPPED LEARNING AND CLT APPROACH: A QUASI- EXPERIMENTAL STUDY AT INTERNATIONAL INFORMATION TECHNOLOGY UNIVERSITY KAZAKHSTAN - Aigerim Abilgazievna, Kereibayeva; Nazym Bolatovna, Baisbay; Takhir Rashitovich, Bekbulatov (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
This study aimed to investigate the effectiveness of integrating a flipped classroom approach with Communicative Language Teaching (CLT) in improving the speaking skills of pre-intermediate students in the context of general English. The research involved two groups, with 16 students in the experimental group and 14 students in the control group. The primary objective was to assess the impact of incorporating the flipped classroom strategy with CLT on students' performance, perceptions, and attitudes towards independent learning of English grammar. Data was collected through pre-tests and post-tests for speaking and writing, as well as a questionnaire measuring students' perceptions and attitudes. The results obtained from the observations and assessments revealed significant improvements in the participants' speaking ability. Furthermore, there was a positive shift in their attitude towards learning English, indicating a favorable response to the flipped instruction and CLT activities. These findings provide substantial evidence for the effectiveness of integrating the flipped classroom approach with CLT in enhancing students' speaking skills and overall learning outcomes. To further advance the understanding in this area, future research should aim to expand upon these findings by investigating their applicability in different general English learning contexts. Exploring the long-term effects of the flipped classroom approach with CLT, as well as assessing its impact on other language skills, would provide a more comprehensive understanding of its effectiveness.